PROGRAM SEKOLAH BAGI PESERTA DIDIK BROKEN HOME DALAM PERSPEKTIF KETAHAHAN PSIKOSOSIAL SISWA DI SD INPRES BONTOBUDDUNG - Abdul, Abdul Basit Ridha; Ahmad Afiif; Ridwan Idris; Alwan Suban; Muh. Anwar HM (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Family disharmony or broken home conditions are a serious challenge to the emotional development and psychosocial resilience of students in the elementary school environment. This study aims to find out the school program and the form of psychological support provided to students who come from disharmonious families. Qualitative approach with case study design. Data collected through interviews with 5 informants (principals, homeroom teachers, Islamic religious education teachers, school committees and students), observation and documentation. Data analysis through reduction, presentation, and drawing conclusions or verification. Data analysis using Nvivo 12 Pro. The credibility of the data is ensured through the source triangulation technique. The results of the research show that the development of students at SD Inpres Bontobuddung is carried out through the role of teachers as functional counselors, the application of a humanist approach based on parental figures, strengthening character through spiritual activities, and partnerships with parents through the RUKOKU program to support student development holistically.